Your Money Or Your Life - Hall, Alvin (Hodder Headline, 2002)
Whether you're daunted by debts, stumped by savings strategies, making plans or moving house, Alvin will help you take charge - for good. He'll show you how to: Recognise your personal spending style - and manage it; Find (practically) painless ways to save money and stick to them...
Keywords: Financial Growth; Non-Fiction; Self-Help